Effect of water filtration infrared-A (wIRA) sauna on inorganic ions excreted through sweat from the human body - Cho, Kang hee; Jung, Sung hun; Choi, Min sun; Jung, Yong jin; Lee, Chang Gu; Choi, Nag choul (Environmental Science and Pollution Research, 2023)
Sweat discharged as a result of exposure to sauna plays an important role in removing inorganic ions accumulated in the body, including heavy metals. In this study, inorganic ions (toxic and nutrient elements) excreted in the form of sweat from the body using a water-filtered infrared-A (wIRA) sauna were determined using inductively coupled plasma sector field mass spectrometry. The analyzed elements included eight toxic elements (Al, As, Be, Cd, Ni, Pb, Ti, and Hg) and 10 nutrient elements (Ca, Co, Cr, Cu, Fe, Mg, Mn, Se, V, and Zn), and their correlations were determined. Analysis of the sweat obtained from 22 people using the wIRA sauna showed a higher inorganic ion concentration than that obtained from conventional activities, such as exercise or the use of wet sauna, and the concentration of toxic elements in sweat was higher in females than in males. Correlation analysis of the ions revealed a correlation between the discharge of toxic elements, such as As, Be, Cd, and Ni, and discharge of Se and V, and Ni was only correlated with Mn. This study provides fundamental information on nutritional element supplementation when using wIRA sauna for detoxification.
Keywords: Cadmium; Environmental Monitoring; Female; Human Body; Humans; Male; Metals, Heavy; Steam Bath; Sweat; Trace Elements; Water; Nutrient; Sauna; Sweat; Toxic elements; Water-filtered infrared-A (wIRA)